Study of Coronary Flow Reserve with Intravenous Use of Microbubbles (Contrast Echocardiography) and Adenosine: Protocol for Clinical Application in Patients Suspected of Having Coronary Heart Disease - Morcerf,Fernando (2002)
OBJECTIVE: To test the feasibility, safety and accuracy of the adenosine protocol in the study of myocardial perfusion with microbubbles contrast echocardiography. METHODS: 81 pts (64 male, 60+11 years) were submitted to contrast echocardiography with PESDA (sonicated solution of albumin 20%-1ml, dextrose 5%-12ml and deca-fluorobutane gas-8ml) to study the myocardial perfusion at rest and after bolus injection of adenosine (6 to 18mg) and to coronary angiography within 1 month each other. For each patient 3 left ventricle perfusion beds were considered (total of 243 territories). 208 territories were analyzed and 35 territories were excluded. PESDA was continuously infused (1-2ml/min), titrated for best myocardial contrast. Triggered (1:1) second harmonic imaging was used. RESULTS: Coronary angiography showed 70 flow limiting (> 75%) lesions and 138 no flow limiting lesions. At rest an obvious myocardium contrast enhancement was seen in at least 1 segment of a territory in all patients. After adenosine injection an unquestionable further increase in myocardial contrast was observed in 136 territories (99%) related to no flow limiting lesions, lasting < 10 s, and a myocardial perfusion defect was detected in 68 territories (97%) related to flow limiting lesions. It was observed only 4 false results. There were no serious complications. CONCLUSION: Myocardial perfusion study with PESDA and adenosine protocol is a practical, safe and accurate method to analyze the coronary flow reserve.